Safety and efficacy of Wharton's jelly‐derived mesenchymal stem cells with teriparatide for osteoporotic vertebral fractures: A phase I/IIa study - Shim, JeongHyun (Stem Cells Transl Med, 2020)
Osteoporotic vertebral compression fractures (OVCFs) are serious health problems. We conducted a randomized, open‐label, phase I/IIa study to determine the feasibility, safety, and effectiveness of Wharton's jelly‐derived mesenchymal stem cells (WJ‐MSCs) and teriparatide (parathyroid hormone 1‐34) in OVCFs. Twenty subjects with recent OVCFs were randomized to teriparatide (20 μg/day, daily subcutaneous injection for 6 months) treatment alone or combined treatment of WJ‐MSCs (intramedullary [4 × 10(7) cells] injection and intravenous [2 × 10(8) cells] injection after 1 week) and teriparatide (20 μg/day, daily subcutaneous injection for 6 months). Fourteen subjects (teriparatide alone, n = 7; combined treatment, n = 7) completed follow‐up assessment (visual analog scale [VAS], Oswestry Disability Index [ODI], Short Form‐36 [SF‐36], bone mineral density [BMD], bone turnover measured by osteocalcin and C‐terminal telopeptide of type 1 collagen, dual‐energy x‐ray absorptiometry [DXA], computed tomography [CT]). Our results show that (a) combined treatment with WJ‐MSCs and teriparatide is feasible and tolerable for the patients with OVCFs; (b) the mean VAS, ODI, and SF‐36 scores significantly improved in the combined treatment group; (c) the level of bone turnover markers were not significantly different between the two groups; (d) BMD T‐scores of spine and hip by DXA increased in both control and experimental groups without a statistical difference; and (e) baseline spine CT images and follow‐up CT images at 6 and 12 months showed better microarchitecture in the combined treatment group. Our results indicate that combined treatment of WJ‐MSCs and teriparatide is feasible and tolerable and has a clinical benefit for fracture healing by promoting bone architecture. Clinical trial registration: https://nedrug.mfds.go.kr/, MFDS: 201600282‐30937.